Repercussions of COVID-19 in hemodialysis patients: a systematic review - Frota Cavalcante, Tahissa; Castro Jansen, Raphaella; Erivelton de Souza Maciel Ferreira, José; Meirú de Lima, Cristefânia; Carolina Cândido Morais, Huana; Pessoa Moreira, Rafaella (Revista Cuidarte, 2022)
• Previous testing for COVID-19 through an individualized approach in hemodialysis patients can be a relevant strategy• A series of nursing actions must be carried out to promote the patients' safety, such as infection control measures, oral hygiene, aspiration of secretions, and vital signs monitoring.• When evaluating a patient with CKD, nurses should be aware of increased values of basal cardiac troponin T or I.• It is essential to identify early risk factors and provide timely treatment for critical cases to reduce mortality and hospitalization in this highly vulnerable group.Introdution: The immunosuppressive state of patients with CKD increases their risk of developing poor clinical outcomes if they acquire COVID-19 infection. Objetive: To identify the scientific evidence about the repercussions of COVID-19 in hemodialysis patients. Materials and méthods: A systematic review was conducted in this study. The databases Cochrane Library, Web of Science, Science Direct, PubMed, and Virtual Health Library were searched to identify relevant studies. The methodological quality of the studies was assessed using the adapted Downs and Black checklist. The review adhered to the PRISMA guidelines. Results:A total of 16 articles were included after the screening process. All articles had a methodological quality higher than 66.8%. The most common repercussions of COVID-19 in hemodialysis patients were the increased mortality rate (75%), development of typical signs and symptoms of the disease such as fever, cough, dyspnea, and fatigue (68.75%), lymphopenia (68.75%), progression to severe acute respiratory syndrome (56.25%), need for mechanical ventilation (50%), and admission to intensive (50%). Conclusión: The hemodialysis patients are more susceptible to COVID-19 infection and, when infected by SARS-CoV-2, these patients have more adverse clinical outcomes, more serious diseases, higher mortality, and worse prognosis than the general population. The repercussions of COVID-19 in hemodialysis patients reveal a need for preventive nursing care in hemodialysis clinics.How to cite this article: Frota Cavalcante Tahissa, Castro Jansen Raphaella, de Souza Maciel Ferreira José Erivelton, Meiru de Lima Cristefânia, Cândido Morais Huana Carolina, Pessoa Moreira Rafaella. Repercussions of COVID-19 in hemodialysis patients: a systematic review. Revista Cuidarte. 2022;13(3):e2695. http://dx.doi.org/10.15649/cuidarte.2695
Keywords: SARS-CoV-2; COVID-19; Hemodialysis; Renal Insufficiency, Chronic; Nursing